Representation of family norms in the short story collection “Amor Untuk Morin” by Richa Miskiyya - Sabrina Andin Nugroho; Tristanti Apriyani (COMMICAST, 2026)
Literary representations of family frequently oscillate between ideals of romantic harmony and depictions of relational fractures, as reflected in “Amor untuk Morin”, a short story collection by Richa Miskiyya, which problematizes the stability of family norms. This study aims to analyze the representation of family norms in the collection through Talcott Parsons’ structural-functional framework, focusing on the extent to which normative functions operate within the familial institution. By situating contemporary Indonesian short fiction within sociological theory, this research contributes to interdisciplinary literary studies that integrate structural-functionalism into textual analysis of family discourse. Employing a qualitative descriptive design, the study applies close reading to identify and interpret narrative structures, dialogues, and symbolic elements, followed by data tabulation and triangulation to ensure analytical validity. The findings demonstrate that family norms in “Amor untuk Morin” are represented as inconsistently implemented; the family is not constructed as a consistently warm or cohesive unit, and normative structures fail to function effectively as institutional mechanisms regulating members’ roles and behaviors. These results indicate a narrative critique of the functionalist ideal of the family and suggest that contemporary literary texts articulate tensions between normative expectations and lived familial realities, thereby reinforcing the analytical relevance of Parsons’ framework in examining shifting constructions of family in modern literature.